Strength Properties and Prediction Model of Cement-Solidified Clay Considering Organic Matter and Curing Temperature - Cao, Yupeng; Zhang, Jing; Xu, Guizhong; Li, Mingdong; Bian, Xia (Frontiers in Materials, 2022)
Cement-solidified clay (CSC) is an important filler material in land reclamation projects. Its strength is greatly affected by its organic matter content and curing temperature. This work reports an experimental study of the unconfined compressive strength (UCS) of CSC with respect to its initial water content w, cement incorporation ratio Aw, organic matter content Co, curing temperature T, and curing duration. A model (UCSOT) for predicting the UCS of CSC is established considering the influence of organic matter and curing temperature. A procedure to implement the model is proposed, and the accuracy of the model is verified. The results show that for a given curing duration, UCS decreases with increases in Co and w, and increases with increases in T and Aw. The influence of organic matter on the UCS is greatly affected by Aw, with a threshold of Aw = 15%. High-temperature curing increases the early and ultimate strengths of CSC, and organic matter increases this temperature sensitivity. Multiple regression characterization using cement content, w, and Co as independent control parameters accurately reflects the UCS at the reference temperature. On this basis, the UCSOT model established here considering the influence of organic matter and curing temperature has universal applicability.